Revitalização urbana do Centro Histórico de Natal/RN à luz do diálogo entre turismo, patrimônio, cultura e criatividade - Melo, Maria Augusta Wanderley Seabra de (2021)
The main objective of this thesis is to point out, based on the experience of the Historic Center of Natal, guidelines for urban revitalization processes, with an emphasis on the dialogue between tourism, culture, heritage and creativity. The study proposes a problematizing investigation of the process of managing the cultural heritage of cities. Therefore, creative forms of management are emphasized, comprising contexts, strategies, actions, causes and consequences, in view of a possible dynamic of intervention in an urban area focused on the practice of cultural tourism, which brings benefits to the population and tourists. In light of the theoretical dialogue between tourism, heritage, culture and creativity, the Historic Center of Natal, RN, Brazil was empirically analyzed, which due to its historicalcultural relevance, has been the target of revitalization policies and interventions with an interest in attracting tourist activity of cultural nature. In methodological terms, this study is characterized as a social research with a qualitative approach, whose data collection was carried out through bibliographical and documentary research, direct observation and semistructured interviews, with different research subjects who relate to the investigated field. For data interpretation, the discourse analysis technique was used. Through the understanding of the historical and empirical context that covers the object of study and the elaboration of the theoretical framework, it was possible to confirm the research hypothesis. It is stated that policies and interventions for the revitalization of the Historic Center of Natal lack integrated actions between the public sector, artists and cultural professionals, the tourist sector, merchants and the local community. The absence of an integrated action makes it difficult for such initiatives to contribute to solving urban socioeconomic problems and diversifying local tourism. This reality demands creative, participatory and interdisciplinary work in the management of the historical area, guided by a strategic set of goals capable of motivating the efforts of the actors involved, in a path of integration, collaboration and co-responsibility. It is up to local leaders the need to define a positive agenda, in order to foster the process of building collective dreams, demonstrating how this scenario will become a reality to overcome the challenges that affect the city, without neglecting the basic needs of the population. It is understood that a city will be attractive to tourists if it is attractive in the eyes of its own population.